Architectural Competition for EPFL Library (Ecole Polytechnique Fédérale de Lausanne – Switzerland): Viewpoint of Technical Panel - Bisbrouck, Marie-Françoise (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
In 2005, the Ecole Polytechnique Fédérale de Lausanne (EPFL) launched an international architectural competition for the construction of a Learning Centre comprising in particular a large library. A technical panel nominated by the contracting authority, comprising experts from the building-engineering and quantity-surveying fields, and including two library-science experts, Mel Collier and Marie-Françoise Bisbrouck, studied the twelve competing architectural projects. The author presents her methodology for the project study, which she founded not purely on functional criteria (number of floors; legibility of various departments; inter-departmental associations; vertical and horizontal circulation; security of collections; design-open-endedness etc.), but also on individual project impact on the built-up architectural environment of the campus site, and the sensation of interior ambience perceived for each project according to the manner in which the interaction and articulation of the various spaces of the programme were proposed. The presentation also includes a comparative table comprising five of the twelve competing projects, highlighting the fact that even though a project may seem to satisfy the majority of the analytical criteria, it is not necessarily functional and attractive in overall terms. The prize-winning project established by the Japanese architecting firm SANAA - an eminently ‘poetic’ work - henceforth leaves EPFL with a question, namely, the degree of ‘adaptability to reality’.